ASN Talent Management: Strategy for Creating Future Leaders - Paroli Paroli (MAR-Ekonomi: Jurnal Manajemen, Akuntansi Dan Rumpun Ilmu Ekonomi, 2023)
Quality leaders are a valuable asset for the sustainability and success of a government or institution. This research will focus on the identification, development and retention of talented individuals in organizations through a holistic talent management approach. This research aims to investigate effective talent management strategies in creating future leaders in the State Civil Service or ASN environment. This research uses a qualitative approach with descriptive methods. The research results show that the implementation of the ASN talent management strategy with a focus on talent identification and development, internal promotion through the cadre formation process, preparation of dynamic career plans, formation of a supportive organizational culture, involvement of talented individuals, as well as continuous evaluation and adjustment, has had an impact positive in creating quality future leaders who are aligned with the organization's long-term goals. This holistic approach provides a strong foundation for the growth of individual talent, strengthens engagement with the organization, and creates an environment that is responsive to change, producing leaders who are not only professionally competent but also committed to the organization's values and vision.